Evaluasi Kebijakan Kurikulum Merdeka dalam Pembelajaran Pendidikan Agama Islam di Sekolah Dasar Islam Amanah Ummah - Sukari, Sukari; Hasan, Ismail (Lembaga Yasin AlSys, 2025)
This study aims to evaluate the implementation of the Kurikulum Merdeka (Independent Curriculum) in Islamic Education (Pendidikan Agama Islam, PAI) at SDI Amanah Ummah. The research uses a qualitative method with a case study approach to deeply explore the curriculum's effectiveness as well as the supporting and inhibiting factors in its application. Data were collected through in-depth interviews with teachers and the school principal, classroom observations, and analysis of curriculum-related documents. The findings indicate that the Kurikulum Merdeka provides teachers with flexibility to design more contextual and student-centered learning. The project-based approach in this curriculum helps students understand Islamic values in an applied manner. However, several challenges were identified, such as varying levels of teacher understanding, limited learning resources, and resistance from some parents toward the new methods being implemented. This study recommends enhancing teacher training, conducting more intensive outreach to parents, and optimizing the use of technology in learning as strategic steps to improve the implementation of the Kurikulum Merdeka at SDI Amanah Ummah.